Immune checkpoint inhibitor-induced isolated adrenocorticotropic hormone deficiency: a systematic review - Wang, Fen; Shi, Xiaoli; Yu, Xuefeng; Yang, Yan (Frontiers in Endocrinology, 2024)
Background Immune checkpoint inhibitor-induced isolated adrenocorticotropic hormone deficiency (IAD) is a rare but potentially fatal disease. Methods We comprehensively searched the PubMed database and made a systematic review of immune checkpoint inhibitor-induced isolated adrenocorticotropic hormone deficiency. If the status of other anterior pituitary hormones was not mentioned, the case was excluded. Results We identified 123 cases diagnosed as immune checkpoint inhibitor-induced IAD, consisting of 44 female and 79 male patients. The average age of these patients was 64.3 ± 12.6 years old, and 67.5% were 60 years old or above. The majority (78.9%) of these patients received anti-programmed cell death protein-1 (anti-PD-1) antibodies or anti-programmed cell death ligand 1 (anti-PD-L1) antibodies or both, and 19.5% received combined therapy, sequential therapy, or both. A total of 26 patients received anti-cytotoxic T lymphocyte antigen 4 antibodies (anti-CTLA-4). The median ICI treatment cycle before the diagnosis of adrenal insufficiency was 8 (6, 12), and the median ICI treatment duration before the diagnosis of adrenal insufficiency was 6 (4, 8) months. Eleven cases developed IAD 1 to 11 months after discontinuation of ICIs. Fatigue and appetite loss were the most common symptoms, and surprisingly, there were two asymptomatic cases of IAD. Most patients (88 cases) had normal pituitary magnetic resonance imaging, only 14 cases reported mild atrophy or swelling pituitary gland, and 21 cases reported no imaging results. Most diagnoses were made by basal hormone levels, and pituitary stimulation tests were performed in only a part of the cases. No cases had been reported of discontinuation of ICI use due to IAD nor had there been any deaths due to IAD. Conclusion IAD was predominant in elderly male patients mainly receiving anti-PD-1 or anti-PD-L1 antibodies. It was sometimes difficult to recognize IAD at first glance since non-specific symptoms were common and asymptomatic cases of IAD were also reported. Although IAD can be deadly, it usually does not affect the continued use of ICIs.